Denmark : Financial Sector Assessment Program-Technical Note-Financial Sector Interconnectedness and Contagion Risk Analysis. (IMF Staff Country Reports; Country Report ;, 2020)
The FSAP developed a novel multi-layer contagion model to analyze financial system interconnectedness using a new and comprehensive database. This new infrastructure, based on securities data and newly-released confidential credit register data, plays a pivotal role in the development of an advanced contagion model that distinguishes the transmission of shocks between eight different exposure types or layers (loans, deposits, reverse repos, covered bonds, other debt securities, equities, unlisted shares, and other claims). The exercise focuses on the banking system (banks and MCIs), and on interconnections through the covered bond market, as the cornerstones of the overall financial system. However, it also includes exposures vis-a-vis non-bank financial institutions (insurer, pension and investment funds) and non-financial sectors (households, corporates), both domestically and abroad. The simulation exercise consists of a series of idiosyncratic shocks, where the default of each node is triggered iteratively. The model introduces a repricing channel on traded securities to capture cascade effects arising from market reactions to changes in an entity's solvency condition.